CMOS multimodal sensor based lab-on-a-chip system for personalized bio-imaging diagnosis - Huang, Xiwei (2015)
The world population is rapidly ageing with proportion of people aged 60-year-old and over, growing faster than any other age groups. Considering the current aging society, there is an emerging need to develop the future diagnosis with portable biomedical devices by bio-instrument miniaturization. The recent development of lab-on-a-chip (LOC) technology has provided a promising integration platform of microfluidic channels, microelectromechanical systems (MEMS), and sensors, which allow non-invasive and near-field sensing functions. The standard complimentary metal-oxide semiconductor (CMOS) process allows a low-cost system-on-chip solution to integrate sensors from multiple domains, which has raised many new design challenges.